Hot topics in sports and athletics (Sports and athletics preparation, performance, and psychology, 2008)
Book Description: Sports and athletics are at once big business, spectator sports, body conditioning, mind expanding and it has been said form the only pages of most newspapers which are truthful and without political agendas. This new book presents articles which are of current interest in the field.